A method based on statistical and experimental analysis for obtaining a biologically optimal solution. (2018) - Yang, Bibo; Yan, Weiwei
Biological forms, shapes, and structures provide optimal solutions for many difficult engineering optimisation problems. This article presents a method based on statistical and experimental analysis to obtain, verify, and reuse optimal solutions from biological organisms. In this method, the form, shape, or structure of a biological example is defined as a factor. A biologically optimal solution comprises one or several such factors. Statistical and experiment analysis are used to verify the contributions of the factors to the excellent performance of the biological organism. Two-sample hypothesis testing and factorial design are applied to the case with single factor and multiple factors, respectively. The procedure of the method is discussed. A case study is presented, which obtains, verifies and reuses a biologically optimal solution (the shape of dragonfly wing) to design the flapping micro air vehicles.